Prospectivity of the multifunctional robotic complex on the basis of the IMR-2M machine for solving the tasks of the Unified State System for Prevention and Elimination of Emergency Situations - Severov, Н.В.; Zheltov, В.Г. (Chrezvychaynye situatsii: obrazovanie i nauka, 2008)
Justification of the creation of a multifunctional robotic complex of heavy class on the basis of the road clearing engineering machine IMR-2M has been carried out and the efficiency of its application for liquidation of consequences of large-scale radiation, chemical, explosion and fire accidents has been evaluated. It is shown that technologically the multifunctional robotic complex is capable of solving a set of tasks in the focus of an accident and in conditions of special risk in the interests of EMERCOM, Minatom and Ministry of Defense of Russia, i.e. it will have practical significance at the level of the Unified State System of Prevention and Elimination of Emergency Situations.